Lifespan Extension Induced by Caffeine in Caenorhabditis elegans is Partially Dependent on Adenosine Signaling - Bridi, Jessika Cristina; Barros, Alexandre Guimarães de Almeida; Sampaio, Letícia Reis; Ferreira, Júlia Castro Damásio; Antunes Soares, Felix Alexandre; Romano-Silva, Marco Aurélio (Frontiers in Aging Neuroscience, 2015)
Caffeine is a widely used psychoactive substance. Studies have shown that caffeine may play a protective role in aging-associated disorders. However, the mechanisms by which caffeine modulates aging are not yet clear. In this study, we have shown that caffeine increases Caenorhabditis elegans lifespan, delays its larval development, reduces reproduction and body length. These phenotypes were partly reversed by worm’s exposure to adenosine, which suggest a putative common target. Moreover, they were dependent on a functional insulin/IGF-1-like pathway. Our results may shed light on new genetic determinants of aging.